Tillandsia mantiqueirae (Bromeliaceae), a New Species from Minas Gerais State, Brazil - Paixão-Souza, Bruno; Silva, Nílber Gonçalves Da; Guimarães, Alessandra Ribeiro; Alves, Ruy José Válka; Costa, Andrea Ferreira Da (Phytotaxa, 2021)
A new species of rupicolous Tillandsia from the Mantiqueira mountain range in Southern Minas Gerais State is described based on morphology and leaf anatomy. This new taxon is close to T. nuptialis. The known distribution and conservation status of this new species are discussed.